2004
DOI: 10.1128/iai.72.5.3077-3080.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Surface Protein C Contributes to Sepsis Caused byStreptococcus pneumoniaein Mice

Abstract: The role of pneumococcal surface protein C (PspC; also called SpsA, CbpA, and Hic) in sepsis by Streptococcus pneumoniae was investigated in a murine infection model. The pspC gene was deleted in strains D39 (type 2) and A66 (type 3), and the mutants were tested by being injected intravenously into mice. The animals infected with the mutant strains showed a significant increase in survival, with the 50% lethal dose up to 250-fold higher than that for the wild type. Our findings indicate that PspC affords a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 21 publications
5
77
0
Order By: Relevance
“…The recruitment of factor H to the surface of pneumococci efficiently prevents the activation of C3b and the complement-mediated opsonophagocytosis of pneumococci (46). The improved survival of pneumococci expressing PspC or Hic in a systemic mouse infection model and in microglial cells provides further evidence for the importance and versatility of PspC in different host niches (29,31). A recent study indicated that carriage isolates, which produce lesser amounts of CPS than the invasive isolates, recruit significantly more factor H than the systemic isolates (53).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The recruitment of factor H to the surface of pneumococci efficiently prevents the activation of C3b and the complement-mediated opsonophagocytosis of pneumococci (46). The improved survival of pneumococci expressing PspC or Hic in a systemic mouse infection model and in microglial cells provides further evidence for the importance and versatility of PspC in different host niches (29,31). A recent study indicated that carriage isolates, which produce lesser amounts of CPS than the invasive isolates, recruit significantly more factor H than the systemic isolates (53).…”
Section: Discussionmentioning
confidence: 78%
“…The lack of PspC in the pneumococci of serotype 2 strain D39 and the lack of Hic in serotype 3 strain A66 attenuated pneumococcal virulence during sepsis. Apparently this defect results in decreased uptake by polymorphonuclear leukocytes (29,30). In addition, pneumococci deficient in PspC, but not wild-type pneumococci, are efficiently killed by microglia cells, which represent the resident phagocytes in the brain (31).…”
mentioning
confidence: 99%
“…This finding is also consistent with a recent study (Orihuela et al, 2004a) that demonstrated that CbpA is not required for the entry of pneumococci into the bloodstream from the lungs, nor for survival in the blood. On another note, CbpA has also been shown to interact with factor H and C3 (Dave et al, 2001;Janulczyk et al, 2000), and to be important in a mouse sepsis model (Iannelli et al, 2004), suggesting a dual role for CbpA in colonization (adherence) and in systemic disease. This might explain why in this study, the expression of cbpA was also significantly upregulated in the lungs and blood, compared to expression in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of factor H by Hic has been shown to efficiently prevent activation of C3b and complement-mediated opsonophagocytosis of pneumococci (Jarva et al, 2004). The improved survival of pneumococci expressing PspC or Hic in a systemic mouse infection model provides further evidence for the versatility and importance of PspC in different host niches (Iannelli et al, 2004;Quin et al, 2005).…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%